Analisis Kebijakan Rehabilitasi Ekonomi Pelabuhan Kamal Pasca Pengoperasian Jembatan Suramadu - Sofiana; Muhammad Roisul Basyar (Public Sphere Review, 2023)
Kamal Port is the main port located in Kamal Village, Bangkalan district, Madura Island, East Java. This port became the center of the crossing of the Madura community from the village of Kamal (Bakalan) to the port of Tanjung Perak (Surabaya). However, with the inauguration of Suramadu Bridge on June 10, 2009, Kamal Harbour experienced a decrease in cruise ship users. The crossing of the ferry, which is 30 minutes longer than the use of the Suramadu Bridge, and the more expensive cost of the Suramudu Bridge are the reasons why people switch from the boat to the bridge. The study aims to analyze the economic rehabilitation policy of Kamal Village as an effort by the government of Bangkalan District to revive the Kamal Port economy. This research will use qualitative descriptive analysis methods with secondary data, where the data is taken based on precise and reliable previous research. The results of this research will refer to the assessment of the potential prospects of the Kamal Port that can be utilized for economic recovery, SWOT analysis as an evaluation of the performance of the Kamal Harbour Maritime Tourism Policy, and economic restoration strategies by assessing the supporting factors suggested by the researchers to improve the Kamal Port economy.